2020
DOI: 10.1080/01652176.2020.1845415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex, age, and season on the variation of blood analytes in a clinically healthyex situpopulation of bottlenose dolphins (Tursiopsspp.)

Abstract: Effects of gender, age, and season on the variation of blood analytes in a clinically healthy ex-situ population of bottlenose dolphins (Tursiops spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is the first work looking into how cetacean plasma polar lipid content is modulated by sex and developmental stage. Several studies have proposed general metabolic changes in T. truncatus metabolism taking place with sex and age 39,40,[45][46][47][48] but this is the first insight into plasma lipid regulation by individual features. Each experimental group (female immature, female adults, male immature and male adults) was shown to display underlined characteristics that made them unique and easily distinguishable from the others in terms of fatty acid and polar lipid compositions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first work looking into how cetacean plasma polar lipid content is modulated by sex and developmental stage. Several studies have proposed general metabolic changes in T. truncatus metabolism taking place with sex and age 39,40,[45][46][47][48] but this is the first insight into plasma lipid regulation by individual features. Each experimental group (female immature, female adults, male immature and male adults) was shown to display underlined characteristics that made them unique and easily distinguishable from the others in terms of fatty acid and polar lipid compositions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Another recent study involving an impressive number of specimens and samples confirmed this influence and identified numerous effects of age and sex on the concentration of several analytes in the plasma of T. truncatus. 48 This study, comprising 1426 blood samples collected from 156 different dolphins, measured 37 analytes in each sample. Mean platelet volume, glucose, blood urea nitrogen, globulins, gamma-glutamyl transpeptidase activity and chloride, which increase with age, while absolute lymphocytes, total protein, alkaline phosphatase activity, creatinine kinase activity, and calcium, all decreased with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The routine biochemical and endocrine data indicated a good health and reproductive condition of the selected individuals. More comprehensive, larger sample size studies on health assessment parameters in relation to season, sex and age for this dolphin species have already been published (Bergfelt et al, 2020;Lauderdale et al, 2021;Nollens et al, 2020) and are not the main objective of the present study.…”
Section: Baseline B-esterase Activities In Healthy Dolphinsmentioning
confidence: 99%
“…Studies on marine mammal welfare in captivity have been increasing over the last 10 years [77,78], and using dolphins as an example, there is now existing research on positive welfare indicators [79][80][81][82][83][84], negative welfare indicators [82,[85][86][87], and a comprehensive assessment framework [88]. Physiological and health-related welfare parameters such as stress hormones [86,89,90], blood profiles [91,92], and pulmonary function [93] have also been examined in captive animals. The controlled environment of the captive setting has also aided in the development of certain hydrophone-video arrays aiming to match cetacean vocalisations to behaviours, thereby decoding their meaning, which would be a critical step in evaluating cetacean welfare [94,95].…”
Section: The Translation Of Welfare Science Information To Marine Mam...mentioning
confidence: 99%